Landscape ecological planning based on change analysis: A case study of mangove restoration in Phu Long – Gia Luan area, Cat Ba Archipelago - Nguyễn, An Thịnh (VNU, 2014)
Mangroves play an important role in coastal zones in many aspects e.g. extremely essential habitats for many species, coastlines protection from natural hazards, and so on. However, in Vietnam, like in other developing countries, these mangrove areas have been destroyed and encroached as a consequence of a poorly planned economic development. The study has been conducted in Phu Long - Gia Luan region, which have the largest mangrove area in the Cat Ba Archipelago Biosphere Reserve, Hai Phong City, Vietnam. The aims of the study are to investigate existing land use conditions, land use changes, as well as driving forces and directions for the changes in order to build a case model of sustainable development; and integrate a mangrove conservation planning into the General Socio - Economic Development Planning Project of Hai Phong City for the period of 2010-2020. The article presents results obtained from study in the period of 2007-2008 in Phu Long - Gia Luan area, including (a) Mangrove area decreased by 98.9 hectares from 1994 (792.3 hectares) to 2006 (693.4 hectares), in which the largest lost is observed in Phu Long southern region, meanwhile Gia Luan region is less changed; (b) There are 12 species belonging to 10 families and two ecological succession series in these mangroves; (c) Planning the area based on principles of landscape ecology for the priority purposes of mangrove restoration up to 2020 so that a mangrove area restored is equal to the area in 1994. The study area is divided into four functional subdivisions: active use subdivision, ecological restoration subdivision, stable use subdivision, and protective subdivision. The value of restored mangrove in Phu Long - Gia Luan is estimated 15,908.45 USD per hectare for shrimp farms through an environment impact assessment and cost-benefit analysis.